2015
DOI: 10.1007/s00167-015-3695-4
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict the size of frequently used autografts in ACL reconstruction?

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 39 publications
3
48
1
Order By: Relevance
“…It has been suggested that detailed preoperative planning helps to determine the most appropriate graft for ACL reconstruction and the ability to preoperatively template the appropriate graft size will minimize graftetunnel mismatch. 20,21,28,29 Factors that influence graft choice include bone morphology, size of the intercondylar notch, and the tibial and femoral footprints of the ACL. 28 Two common grafts that frequently are used are HS and BPTB grafts, and excellent results can be obtained with both if surgical techniques are consistently applied.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that detailed preoperative planning helps to determine the most appropriate graft for ACL reconstruction and the ability to preoperatively template the appropriate graft size will minimize graftetunnel mismatch. 20,21,28,29 Factors that influence graft choice include bone morphology, size of the intercondylar notch, and the tibial and femoral footprints of the ACL. 28 Two common grafts that frequently are used are HS and BPTB grafts, and excellent results can be obtained with both if surgical techniques are consistently applied.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on 62 patients that underwent ACL surgery, Zakko et al observed that preoperative MRI measurements of QT, PT and hamstring graft size are highly reliable with moderate-to-good accuracy. Further, a significant correlation between patient anthropometric data and the thicknesses of both QT and PT was observed 18 . Our results are consistent with previous MRI studies demonstrating weakly positive correlations between QT thickness and anthropometric data.…”
Section: Ns=no Significant Differencesmentioning
confidence: 94%
“…PT thickness was measured three times, respectively 1 cm below the lower border of the patella (P1), at the middle of the patellar tendon (P2) and 1 cm above the upper border of the tibial tubercle portion (P3), respectively, as described by Chang et al 14 . QT was measured at three levels, at distances of 10 (Q1), 20 (Q2) and 30 mm (Q3) from the superior pole of the patella 18 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, patellar tendon length was measured from the posterior insertion of the tendon to the tibia to the posterior insertion of the tendon to the patella. PT thickness was measured three times, respectively 1 cm below the lower border of the patella (P1), at the middle of the patellar tendon (P2) and 1 cm above the upper border of the tibial tubercle portion (P3), respectively, as described by Chang et al 14 . QT was measured at three levels, at distances of 10 (Q1), 20 (Q2) and 30 mm (Q3) from the superior pole of the patella 18 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%